Pembinaan Karakter Sebagai Upaya Pencegahan Bullying di Sanggar Bimbingan Muhammadiyah Kampung Bharu Kuala Lumpur Malaysia - Iskarimah, Rizqi Iskarimah; Heriyana, Tio; Hermawan; Hadiana, Oman; Nur, Hana Astria (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2024)
As parents must have the main source of education for their children, because parents have an essential role in character building children. Prevention of bullying is the most important issue in ensuring the atmosphere is in a harmonious and positive environment for all individuals, especially in educational environments such as guidance studios. This community service activity was carried out at SB Muhammadiyah Kampung Bharu Kuala Lumpur Malaysia by conducting sharing about the importance of preventing bullying in the community. The method of community service uses the socialization method.. The implementation of character building socialization as an effort to prevent bullying lasted for one day, precisely at the Kampung Bharu Guidance Studio, Kuala Lumpur, Malaysia, attended by 30 participants and managers of the Kampung Bharu studio. The importance of character building in children as an effort to prevent bullying at the Kampung Bharu Guidance Studio, Kuala Lumpur, is very important because as informal education must have a role and strategy of course in forming the character it has, so that it can be an effective defense process against Bullying behavior. It is hoped that this character building can be an initial step in overcoming potential bullying cases among students.